Euthanasia dan Martabat Manusia: Kajian Hukum, Medis, Etis, dan Moral Katolik - Tjang, Yanto Sandy; Acin, Mayong Andreas (Jurnal Pelayanan Pastoral, 2025)
This study aims to comprehensively analyze the phenomenon of euthanasia through a multidimensional approach encompassing legal, medical, ethical, and Catholic moral perspectives, placing human dignity at the core of reflection. The issue of euthanasia presents a complex dilemma between respect for individual autonomy and the moral duty to uphold the universal value of life. In Indonesia, euthanasia is strictly prohibited as it violates the constitutional and criminal law principles protecting the right to life as a fundamental human right. Conversely, countries such as the Netherlands, Belgium, and Canada have legalized euthanasia under stringent regulations requiring patient consent, terminal medical conditions, and professional responsibility from physicians. From a medical ethics perspective, the principles of autonomy, beneficence, non-maleficence, and justice form the moral foundation for end-of-life decision-making. The Catholic Church, through Evangelium Vitae and the Catechism of the Catholic Church, rejects active euthanasia as contrary to the sanctity of life and human dignity as imago Dei. However, discontinuing extraordinary or disproportionate medical treatment is considered permissible under the principle of proportionality and respect for natural death. The study concludes that a multidimensional approach offers a balanced framework for understanding euthanasia, safeguarding human dignity, and promoting palliative care as a more ethical, humane, and just alternative.